Certain Syntagmatic Relations between Legal Terms of Obligation in the Ukrainian, English and Portuguese Languages (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article focuses on the analysis of certain syntagmatic relations as linear relations between the legal terms of the Ukrainian, English and Portuguese languages in the area of law of obligations.  The syntagmatic relations get analysed within the minimum syntactical unit to be further differentiated with view to the context and coordination. The context as presented herein anticipates, without limitation, a kind as follows: lexical, semantic, grammatical, linguistic and extra-linguistic.
Keywords: syntagmatic relations; a legal term of obligations; lexical; semantic; grammatical; linguistic and extra-linguistic contexts